PENGEMBANGAN MULTIMEDIA BERBASIS KEARIFAN LOKAL TERINTEGRASI HOTS PADA MATERI PERPINDAHAN KALOR KELAS V DI SDN SIDOREJO: pengembangan - Sufi Cahyo Wulandari; Titi Anjarini; Nur Ngazizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to: 1) Develop a product in the form of a multimedia product based on local wisdom integrated with HOTS for heat transfer for fifth grade students at Sidorejo Elementary School. 2) Determine the feasibility of a multimedia product based on local wisdom integrated with HOTS for heat transfer for fifth grade students at Sidorejo Elementary School.This research and development model uses the ADDIE model. The data collection techniques used in this research include: 1) Interviews, 2) Observations, 3) Student response questionnaires, 4) Learning implementation, 5) Expert questionnaires, and 6) tests. Data analysis was conducted by calculating validity, student response questionnaire results, learning implementation results, and tests.The results of this development research are 1) Development of multimedia based on local wisdom integrated with HOTS for heat transfer material for grade V of SDN Sidorejo. 2) The feasibility of multimedia based on local wisdom integrated with HOTS for heat transfer material for grade V of SDN Sidorejo includes 3 aspects, namely validation, practicality, effectiveness. Based on the validation aspect, the experts obtained an average of 90% with very valid criteria. In the practicality aspect, based on the results of student responses, an average of 87.5% was obtained with very practical criteria and the results of learning implementation obtained an average percentage of 90.5% with very practical criteria. In the effectiveness aspect, based on the test results after using multimedia, an average N-gain of 0.845 was obtained with a high category and an interpretation of the N-gain percentage of 84.5% with very effective criteria. Therefore, it can be concluded that multimedia based on local wisdom integrated with HOTS is declared suitable for use in learning.